An Innovative Multilevel Test for Hemoglobinopathies: TGA/Chemometrics Simultaneously Identifies and Classifies Sickle Cell Disease From Thalassemia - Risoluti, Roberta; Caprari, Patrizia; Gullifa, Giuseppina; Massimi, Sara; Maffei, Laura; Sorrentino, Francesco; Carcassi, Elena; Materazzi, Stefano (Frontiers in Molecular Biosciences, 2020)
Introduction - Hemoglobinopathies are the most common genetic disorder wordlwide and because of migrations are become an emerging global health problem. Screening programmes for Sickle cell disease and Thalassemia have been implemented in some countries, but are not a common practice, due to a lack in the accuracy of the methods and to the costs of the analyses. Objectives - The objective of this study was the application of the thermogravimetry coupled to chemometrics as new screening method to perform an early diagnosis of thalassemia and sickle cell disease. Methods - Whole blood samples (30 µL) from sickle cell anemia and thalassemia patients were analyzed using the thermobalance TG7 and the resulting curves were compared with those of healthy individuals. A chemometric approach based on Principal Components Analysis (PCA) was exploited to enhance correlation between thermogravimetric profiles and a model of prediction by Partial Least Square Discriminant Analysis (PLS-DA) was developed and validated. Results - The characteristic profile of the blood sample thermal decomposition and the first derivative of the TG curve showed that patients were clearly distinguished from healthy individuals as a result of different amounts of water and corpuscular fraction of blood. The chemometric approach based on PCA allowed a quick identification of differences between healthy subjects and patients and also between thalassemic and sickle cell anemia subjects.